ANALISIS PRAKTEK JUAL BELI BARANG SITAAN DALAM PERSPEKTIF HUKUM ISLAM : (Studi Kasus di Pondok Pesantren Raudhatul Ulum 1 Ganjaran Gondanglegi Malang) - Roisul Adib; Sadam husin (Ahwal Al-Syakhsiyyah Fakultas Syariah - Universitas Al-Qolam Malang, 2023)
Buying and selling is one of the economic systems that can be carried out by humans to get the desired property or goods without having to harm one of the parties involved in buying and selling, namely the trader and the buyer whoever it is. However, there are cases of buying and selling carried out at Islamic boarding schools, where goods in the form of cell phones confiscated by the boarding school security council are then traded at prices that are affordable but not cheap. In this case there was a transfer of ownership from the santri to the Islamic boarding school. So that the rules of buying and selling in Islamic law are correct, namely in the rules the object of buying and selling must be the property of the seller himself or be represented according to the buying and selling theory explained by Jumhurul Ulama'. The review of Islamic law regarding the sale and purchase of confiscated HP at Islamic boarding schools is that the transaction contract for the sale and purchase of confiscated HP is legal, as stated in the theory of buying and selling in Islamic law, both terms and conditions in the sale and purchase have been fulfilled and according to the rules. So that the sale and purchase of confiscated HP can be carried out, because it meets the requirements and pillars of buying and selling in Islamic law